2021
DOI: 10.1007/s11469-021-00638-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice, and Fear of COVID-19: an Online-Based Cross-cultural Study

Abstract: The study aimed to measure Knowledge, Attitude, and Practice (KAP) and fear level towards COVID-19 and explore its cross-cultural variances in knowledge by sociodemographic factors among the general population of 8 different countries over 5 continents. It was a cross-sectional online survey. This survey was conducted in April 2020 among 1296 participants using the “Google Form” platform. Considering the social distancing formula and pandemic situation, we collect data using popular social media networks. Univ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
2
32
3
Order By: Relevance
“…According to the results, the participants, regardless of gender or age, had a good understanding of COVID-19, in contrast to previous studies revealing relatively less knowledge about COVID-19 disease transmission [ 38 , 39 , 40 ], but similar to Kasemy et al’s research [ 41 ]. Moreover, there was no significant difference in knowledge as a function of education, age, or gender, unlike prior studies [ 13 , 41 , 42 ]. It was inferred that most participants had higher education levels, as there were only 9.71% participants without a bachelor’s degree; in addition, the general public’s awareness of the information provided by the TCDC was facilitated by its availability on various social media platforms and TV channels.…”
Section: Discussioncontrasting
confidence: 91%
“…According to the results, the participants, regardless of gender or age, had a good understanding of COVID-19, in contrast to previous studies revealing relatively less knowledge about COVID-19 disease transmission [ 38 , 39 , 40 ], but similar to Kasemy et al’s research [ 41 ]. Moreover, there was no significant difference in knowledge as a function of education, age, or gender, unlike prior studies [ 13 , 41 , 42 ]. It was inferred that most participants had higher education levels, as there were only 9.71% participants without a bachelor’s degree; in addition, the general public’s awareness of the information provided by the TCDC was facilitated by its availability on various social media platforms and TV channels.…”
Section: Discussioncontrasting
confidence: 91%
“…The findings highlight differences for all the outcome variables. Although it is important to interpret these results with caution given the unequal sample sizes recruited from the three countries, these findings are consistent with the recent literature on COVID‐19, which showed that respondents from the Middle East expressed more fear when compared to their European counterparts (Ali et al, 2021 ). The higher the collectivistic orientation of a society, the higher the perceived vulnerability to infectious diseases.…”
Section: Discussionsupporting
confidence: 88%
“…A validated and previously employed “Fear of COVID-19 Scale” (FCV) was utilized to measure fear of coronavirus-19 [ 10 , 49 ]. This questionnaire is a single-dimensional seven-item, 5-point Likert scale, produced by Ahorsu et al [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among other psychological responses to the current COVID-19 pandemic, fear is common and potentially distressful [ 10 , 37 ]. We can define fear as an adaptive emotion fundamental for survival, which distributes to prepare the individual for behavioural responses to potential danger [ 24 ].…”
Section: Introductionmentioning
confidence: 99%